PENGARUH HEPATOPROTEKTIF EKSTRAK DAN INFUSADAUN KELOR (Moringa oleifera) TERHADAP KADAR SGOT DAN SGPT HATI MENCIT (Mus musculus) GALUR DDYOBESITAS YANG DIINDUKSI 2-NITROPROPANE - Fakhri Haidar Anis, (2019)
Obesity is correlated with death rates from liver cancer. Moringa plants contain flavonoids namely quercetin which has the potential as a hepatoprotective agent. The purpose of this study was to determine the effect of Moringa leaf extract and infusion on the levels of SGOT and SGPT in liver of obese Mice induced by 2Nitropropane (2-NP). The method used was a post control group design only using male obesity mice divided into 4 groups. K1 and K2 given high-fat high-protein feed and drink ad libitum; K3 is given moringa leaf extract 4 mg/day (0.2 ml); K4 is given 40 mg moringa leaf infusion/day (0.2 ml). All were treated for 20 days. Then, groups K2, K3 and K4 are injected intraperitoneally 2-NP 0.02 mg/KgBB. The results obtained have a significant effect on Moringa leaf extract and infusion administration on liver SGPT levels. K1 is significant towards K2 of (p=0,00). K2 was significant towards K3 (p=0,02). K2 is significant towards K4 of (p=0,005). However, K3 was insignificant to K4 of (p=0,234). However, the results obtained on SGOT levels were of significance (p=0,969), which meant that there was no significant effect although on average it has an effect. The conclusion is that Moringa leaf extract and infusion affect SGPT levels in mice induced by 2-NP obesity.